Kuasa Perempuan Bali: Peran dan Kapasitas Perempuan Bali dalam Menghadapi Erupsi Gunung Agung - Megasari Noer Fatanti; Ary Budiyanto; I Kadek Yudi Astawan; Cindy Nirmala Wijaya (Sosioglobal, 2021)
Women are one part of a vulnerable group in the event of a disaster. Data from the National Disaster Management Agency (BNPB) states that women have a 14 times higher risk of becoming victims of disasters than adult men. This is due to the instinct of women who want to protect their families and children, which often makes them neglect their own safety. Therefore, providing access to information and disaster education is important to reduce the number of victims when a disaster occurs. This research aims to how the preparedness of women in the village of Besakih in facing the risk of the eruption of Mount Agung in Karangasem Regency, Bali. Through ethnographic methods with live-in strategy for gathering data during July-October 2019, this research found some potential of Balinese women when facing disasters. The character of Balinese women who are independent, tough and adaptive is their key to survive in a disaster situation. In addition, the woman of Besakih Village claimed to be actively seeking information on Mount Agung disaster through Facebook as a form of self-mitigation before the disaster occurred. Research recommendations are directed at training to increase women's capacity such as recognizing the initial symptoms of disasters, how to find and select correct information on social media related to disasters, and to play an active role as an agent of disaster vulnerability in the family.